Nutrient timing: A garage door of opportunity? - Arent, S. M.; Cintineo, H. P.; McFadden, B. A.; Chandler, A. J.; Arent, M. A. (Nutrients, 2020)
Nutrient timing involves manipulation of nutrient consumption at specific times in and around exercise bouts in an effort to improve performance, recovery, and adaptation. Its historical perspective centered on ingestion during exercise and grew to include pre- and post-training periods. As research continued, translational focus remained primarily on the impact and outcomes related to nutrient consumption during one specific time period to the exclusion of all others. Additionally, there seemed to be increasing emphasis on outcomes related to hypertrophy and strength at the expense of other potentially more impactful performance measures. As consumption of nutrients does not occur at only one time point in the day, the effect and impact of energy and macronutrient availability becomes an important consideration in determining timing of additional nutrients in and around training and competition. This further complicates the confining of the definition of "nutrient timing" to one very specific moment in time at the exclusion of all other time points. As such, this review suggests a new perspective built on evidence of the interconnectedness of nutrient impact and provides a pragmatic approach to help frame nutrient timing more inclusively. Using this approach, it is argued that the concept of nutrient timing is constrained by reliance on interpretation of an "anabolic window" and may be better viewed as a "garage door of opportunity" to positively impact performance, recovery, and athlete availability.